2019
DOI: 10.14745/ccdr.v45i09a01
|View full text |Cite
|
Sign up to set email alerts
|

Use of a case–control study and control bank to investigate an outbreak of locally acquired cyclosporiasis in Canada, 2016

Abstract: Background: Cyclospora is an intestinal parasite that is not endemic in Canada. However, national outbreaks of locally acquired cases have been reported since 2013. These outbreaks were suspected to be associated with consumption of produce imported from countries where Cyclospora is endemic. Identification of the source can be challenging because of reporting delays and limited traceability of produce. Objective: To report on a national outbreak of locally acquired cyclosporiasis, highlight the challenges of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In this study, the response rate for the control bank was almost 70 times greater than that of the landline or cell phone samples. Similarly, in a recent case-control study related to an outbreak of cyclosporiasis, the response rate for the control bank was 60% compared to only 24% via random digit dialling [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the response rate for the control bank was almost 70 times greater than that of the landline or cell phone samples. Similarly, in a recent case-control study related to an outbreak of cyclosporiasis, the response rate for the control bank was 60% compared to only 24% via random digit dialling [20].…”
Section: Discussionmentioning
confidence: 99%
“…Response rates for random digit dialling methods have seen a dramatic decline in recent years, due in part to the popularity of caller identification [15, 18, 19]. The use of a pre-established control bank of consenting participants could result in a higher response rate than that of random-digit dialling or calling listed numbers within the general population, potentially reducing time and cost to complete a case-control study [20]. A further limitation for random digit dialling methods is the lack of ability to make targeted calls, adding an additional challenge to recruiting controls in the context of a matched study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case–control study of an outbreak in Canada, a total of 87 (1 hospitalized) locally acquired cases in four provinces from May to August 2016 were examined [ 43 ]. Although the study was not able to identify the exact source of the outbreak, case exposure identified some possible foods, with imported blackberries from Mexico being the most likely source of infection.…”
Section: Epidemiologymentioning
confidence: 99%
“…In Canada, the first cyclosporiasis outbreak was reported in 1996 [2] prior to becoming a nationally notifiable disease in 2000. Multijurisdictional foodborne outbreaks of locally acquired cases have been declared yearly during the spring or summer months since 2013 [3]. Previous Canadian foodborne cyclosporiasis outbreaks have been associated with a variety of food vehicles imported from endemic regions, including fresh berries (e.g., raspberries, blackberries) [3][4][5][6], fresh herbs (e.g., basil, cilantro) [7,8], leafy greens [9], and other fresh produce (e.g., sugar snap peas) [10].…”
Section: Introductionmentioning
confidence: 99%